The use of brome grass in fattening yearling heifers as compared to fattening in a dry lot. - Smith, E.F.; Cox, R.F.; Good, D.L.; Mackintosh, D.L. (Kansas Agricultural Experiment Station, 2012)
The purpose of this study is to develop a system of fattening heifers for feeders who do not have native pasture or have no pasture. The plan of production is to buy good quality heifer calves in the fall, winter them well (which entails the feeding of about two pounds of grain per head daily in addition to roughage and protein). Following the winter period there are three alternatives being tested: full feed in dry lot; full feed on brome grass pasture; graze brome pasture early, then full feed in dry lot.
Keywords: Beef; Brome grass; Heifers; Dry lot